Estudo de prevenção e controle da COVID-19: percepção e práticas no cotidiano das orientações médico-científicas pela população de um território de abrangência da Atenção Primária à Saúde no município de São Luís, Maranhão - MELO, Joana Carolyne de Oliveira Felix Portela (2022)
Introduction: The global context of public health emergency caused by the COVID-19 pandemic challenges different countries to think about strategies for the prevention and control of infection by Sars-CoV-2. In this context, Primary Health Care is a strategic space for the provision of comprehensive care. Objective: To analyze how the population of the territories covered by the PHC perceive and translate everyday practices in the individual, family and collective spheres regarding the prevention and control measures of COVID-19. Methodology: a quantitative-qualitative, descriptive and transversal research was used. The study was carried out in the territories covered by the Primary Care of the Amar Health Center - São Luís - MA. For the research instrument, the structured interview modality was chosen. The instruments were applied in the first stage through a semi-structured online questionnaire, and in the second stage, face-to-face dialogue interviews were applied. Results: The study sample consisted of people aged between 18 and 82 years, with a predominance of 18 to 30 years old, women, married, complete medium education, self-declared brown, families composed of 1 to 3 people per household, households with 3 rooms, running water and only 1 bathroom. In the qualitative analysis, the Descending Hierarchical Classification identified five classes that generated two categories: Health Education during the Coronavirus Pandemic; Strategies to fight the Coronavirus. The Correspondence Factor Analysis performed a cross between the text variables and their classes, making it possible to identify by Similitude that Television was the most accessed source, with a good level of trust and an excellent level of information feeling. And that although health professionals were accessed by a minority of respondents, there was no negative impact on the good levels of trust and feeling of information that aroused in the population. The degree of importance and credibility given to social isolation is also observed, however the low-income profile of the families prevented the full adoption of this measure, due to the continuous need to go out to work. Conclusion: It is inferred that studies on perceptions and practices, in a pandemic period, make it possible to better understand the experience lived in a unique and singular way of each subject, in order to plan educational and informational actions for the population, consequently reducing their possible impacts.